A formação territorial do Brejo paraibano e a luta pela terra: o caso do assentamento Nossa Senhora de Fátima - Rodrigues, Leandro Paiva do Monte (2012)
The peasant struggle for land in Brazil is not new, but was always put aside a theme in Brazilian politics. This struggle has taken different forms, especially after the second half of the twentieth century. The objective of this study is to understand the peasant struggle for land and life on earth from the town of Bananeiras, the state of Paraiba, through a case study of a settlement project, the Our Lady of Fatima in the light of geo-historical process of formation of the Territorial Brejo Paraiba. The municipality of Banana is located in the Brejo Paraiba which is considered an exception area, both by physiographic conditions and by different ways of producing space for the rest of the Agreste, where this space is located subunit. With regard to the agrarian question, Brejo reproduces the contradictions found in the field and stands out as the scene of conflicts over land and labor and the role played by the Catholic Church (through the Pastoral Land Commission of the Diocese of Guarabira and actions of local parishes), and the trade union movement. For this study, from the methodological choices were made several field studies, literature and documentary. The category of analysis is the geographic territory. We understand that this category makes it possible to understand the struggle between capital and labor in the field. We consider the settlement as a territory of hope, that is, as he won for workers and that represents both a break with the form of social organization, economic and political pre-existing, as a form of resistance to domination of the capitalist mode of production in field. As agents, actors and protagonists in the struggle for land in Paraíba Brejo, the paper highlights, in addition to the peasant class, the Peasant Leagues, the Pastoral Land Commission and the Rural Unionism. Then, recalls the history of the struggle for land that gave rise to the Settlement Project Our Lady of Fatima and has internal and external dynamics of the settlement, its achievements and its contradictions.